Jeremiah and God's Plans of Well-being - Green, Barbara, 1946- (Book collections on Project MUSE., 2013)
A fresh treatment of a complex biblical text and the prophet Jeremiah as a literary figure. The author explores Jeremiah as a literary persona of the biblical book through seven periods of his prophetic ministry, focusing on the concerns and circumstances that shaped his struggles.